Rat Nasal Respiratory Mucosa-Derived Ectomesenchymal Stem Cells Differentiate into Schwann-Like Cells Promoting the Differentiation of PC12 Cells and Forming Myelin In Vitro - Jian Zhang; Xin Gao; Hongjun Zou; Jinbo Liu; Zhijian Zhang (Stem Cells International)
Schwann cell (SC) transplantation as a cell-based therapy can enhance peripheral and central nerve repair experimentally, but it is limited by the donor site morbidity for clinical application. We investigated weather respiratory mucosa stem cells (REMSCs), a kind of ectomesenchymal stem cells (EMSCs), isolated from rat nasal septum can differentiate into functional Schwann-like cells (SC-like cells). REMSCs proliferated quickly in vitro and expressed the neural crest markers (nestin, vimentin, SOX10, and CD44). Treated with a mixture of glial growth factors for 7 days, REMSCs differentiated into SC-like cells. The differentiated REMSCs (dREMSCs) exhibited a spindle-like morphology similar to SC cells. Immunocytochemical staining and Western blotting indicated that SC-like cells expressed the glial markers (GFAP, S100β, Galc, and P75) and CNPase. When cocultured with dREMSCs for 5 days, PC12 cells differentiated into mature neuron-like cells with long neurites. More importantly, dREMSCs could form myelin structures with the neurites of PC12 cells at 21 days in vitro. Our data indicated that REMSCs, a kind of EMSCs, could differentiate into SC-like cells and have the ability to promote the differentiation of PC12 cells and form myelin in vitro.